Building Integration of Renewable Energy Systems towards Zero or Nearly Zero Energy Buildings - Kalogirou, Soteris A. (My University, 2012)
With buildings accounting for 40% of primary energy requirements in EU and the implementation of the Energy Performance of Buildings Directive (EPBD), developing effective energy alternatives for buildings is imperative. The increasing role for renewables implies that solar thermal systems (STS) and photovoltaics (PV) will have a main role as they contribute directly to the heating and cooling of buildings and the provision of electricity and domestic hot water. Meeting building electrical and thermal loads will be primarily achieved through an extensive use of renewables, following standard building energy saving measures, such as good insulation or advanced glazing systems. These systems are typically mounted on building roofs with no attempt to incorporate them into the building envelope creating aesthetic challenges, space availability issues and envelope integrity problems. This paper aims to give a survey of possible solutions of PV and STS integration on the building roofs and façades. The advantages of integration are quantified and suggestions are given to address the possible problems created.
Keywords: Energy Performance of Buildings Directive; Solar thermal systems; Photovoltaics